1983
DOI: 10.1002/j.1537-2197.1983.tb07878.x
|View full text |Cite
|
Sign up to set email alerts
|

Floral Organogenesis in Five Genera of the Marantaceae and in Canna (Cannaceae)

Abstract: The paired flowers of all species of the Marantaceae studied, except Monotagma plurispicatum, are produced through the division of an apical meristem with a tunica‐corpus structure. The solitary flowers of M. plurispicatum develop from a similar meristem which does not bifurcate. The paired flowers of Canna indica are produced in the axil of a florescence bract through the formation of a bract and an axillary flower on the side of the primordium which gives rise to the largest flower of the pair. The sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
1
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 10 publications
2
27
1
1
Order By: Relevance
“…Th e observations presented here on fl oral vasculature and ontogeny in Canna indica indicate that the labellum and functional stamen incorporate elements of two androecial members each, rather than three, one or half, as suggested by previous studies of Cannaceae (Th ompson 1933, Pai 1963, Kirchoff 1983b, Almeida 2013.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Th e observations presented here on fl oral vasculature and ontogeny in Canna indica indicate that the labellum and functional stamen incorporate elements of two androecial members each, rather than three, one or half, as suggested by previous studies of Cannaceae (Th ompson 1933, Pai 1963, Kirchoff 1983b, Almeida 2013.…”
Section: Discussionsupporting
confidence: 69%
“…Several morphologists have claimed that the stamen of Canna belongs to the inner androecial whorl (Eichler 1875, Rao and Donde 1955, Pai 1963, Kirchoff 1983b). Costerus (1916,1917) suggested that the anther and petaloid appendage are members of diff erent whorls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Marantaceae and Cannaceae consistently have conspicuously asymmetric flowers with corolla, androecium and gynoecium involved, especially elaborate in Marantaceae (Kirchoff, 1983;Kress, 1990;Classen-Bockhoff & Heller, 2008). They may be seen as an elaboration of monosymmetric flowers as in the other six families of the order, of which a few Zingiberaceae also have asymmetric flowers (Hedychium) (Kress, 1990).…”
Section: Malpighialesmentioning
confidence: 96%
“…In vertebrates the organisational internal asymmetry is not conspicuous externally; however, some specialized groups also have an external non-enantiomorphic asymmetry, such as snail-eating snakes with asymmetric jaws (Hoso et al, 2007). If enantiomorphic flowers occur on one individual, they are often components of a system with pendulum symmetry (Goebel, 1908;Endress, 1999;Kirchoff, 2003;Hardy et al, 2004).…”
Section: Diverse Manifestations Of Asymmetry In Flowersmentioning
confidence: 99%